The Predictors of Employee Performance in the Face of Rapidly Change During Pandemic Era - Elfitra Azliyanti; Purbo Jadmiko; Lindawati Lindawati (Jurnal Manajemen Universitas Bung Hatta, 2023)
Pandemic era has change all of life aspects in the world, including education institutions like universities. Lectures as a central of learning process must play their part on creating globally competitive collage students. One of the impact pandemics era is teaching process become online learning and no longer in campus as previously. The rapidly change requires lecturers to improve their skill at technology, increase their creativity and also must follow the changes. All of the predictor will have an impact to letcures performance. The research methodology used explanatory through four hypothesis testing either direct and mediation effect. The object and population use at study are lecturers at Universitas Bung Hatta, Padang. Purposive sampling use to find the sample with some criteria amd the criteria is who have a working period of > 1 year. the method of sampling in this study used the Slovin formula with 167 samples. STATA 12  wa the analysis technique used in this study. From the data testing, all of the hyphoteses accepted.